Needs Assessment Study in Science Education: Sample of Turkey - Z. Ozdilek; M. Ozkan (University of Sofia, 2008)
A needs assessment process was conducted to determine the difficulties and requirements of a science unit as an example how needs assessment process can be used in science education in Turkey. A 40-item teacher questionnaire containing four dimensions related to a chemistry unit named "Travel to the Inner Structure of Matter" as presented in the current curriculum materials was administered. The questionnaire was completed by 130 elementary school science teachers in order to get their views and suggestions for revising the unit. The Cronbach's alpha reliability coefficient was found to be .93 for the questionnaire. Descriptive statistical methods were also used in analyzing the survey data. It was concluded that science teachers recognize some deficiencies in the unit's aims and goals, teaching program, teaching strategies, and evaluation procedures. As a result of this study, it is suggested that instructional designs and revisions of existing materials for science units can be undertaken using a deliberate needs assessment process-in particular a process that -relies both on the existing research related to a topic and teachers' expert input regarding instruction.